Stock Investing For Dummies - Mladjenovic, Paul (Hoboken, New Jersey John Wiley & Sons, Inc., 2013)
This practical guide gives you proven strategies for selecting and managing profitable investments in either a bear or bull market. Discover how to navigate the new economic landscape, and choose the right stocks for different situations.
Includes Index and Illustrations.
Keywords: Stocks